(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
In the last years, the European Union has vigorously sought to curb the ever-spreading production and use of single-use plastic, underpinned by persistent concerns over its adverse environmental and health impacts. The instruments employed include Directive (EU) 2019/904 and, more recently, Regulation (EU) 2025/40 on plastic packaging. The former has not only triggered acute debate, but has also unveiled divergent approaches and standpoints across Member States. This paper hence illustrates its regulatory cornerstones and explores its transposition, as well as the regulation of plastic more broadly, in both Italy and Spain, with a particular focus on extended producer responsibility as a pivotal mechanism of circular economy.